2008
DOI: 10.1038/jcbfm.2008.21
|View full text |Cite
|
Sign up to set email alerts
|

Acute Functional Recovery of Cerebral Blood Flow after Forebrain Ischemia in Rat

Abstract: After complete cerebral ischemia, the postischemic blood flow response to functional activation is severely attenuated for several hours. However, little is known about the spatial and temporal extent of the blood flow response in the acute postischemic period after incomplete cerebral ischemia. To investigate the relative cerebral blood flow (rCBF) response in the somatosensory cortex of rat to controlled vibrissae stimulation after transient incomplete ischemia (15-min bilateral common carotid artery occlusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…This thresholding technique is common practice in the analysis of VSD optical imaging data to find intensity contours (Wallace and Sakmann, 2008). It has been reported that with different thresholding criteria the activation boundary shifts only slightly (not more than 8%) in VSD (Chen et al, 2005) and intrinsic (Tsytsarev et al, 2004;Vnek et al, 1999;Zhou et al, 2008) optical imaging. Fifty percent thresholding of the maximum signal, as used in the current study, has been confirmed to be effective in barrel field VSD optical imaging by Wallace and Sakmann (2008).…”
Section: Methodsmentioning
confidence: 99%
“…This thresholding technique is common practice in the analysis of VSD optical imaging data to find intensity contours (Wallace and Sakmann, 2008). It has been reported that with different thresholding criteria the activation boundary shifts only slightly (not more than 8%) in VSD (Chen et al, 2005) and intrinsic (Tsytsarev et al, 2004;Vnek et al, 1999;Zhou et al, 2008) optical imaging. Fifty percent thresholding of the maximum signal, as used in the current study, has been confirmed to be effective in barrel field VSD optical imaging by Wallace and Sakmann (2008).…”
Section: Methodsmentioning
confidence: 99%
“…These include: Durduran et al 21 which used DCS to monitor cerebrovascular hemodynamics in acute stroke patients, Buckley et al, 22 which used DCS to monitor cerebral hemodynamics in premature infants undergoing positional intervention, and Zhou et al, 25 which monitored cerebral hemodynamics in piglet brains following closed head injury and recently it has been used to monitor cerebral hemodynamics in neonatal, who have undergone cardiac surgery. 26 New recent studies have demonstrated non-contact DCS method for blood flow measurement 27 thus enabling standoff measurement of hemorrhage in the future. If a bleed or occlusion occurs, blood flow in the brain slows down and is detected as a slowing in DCS correlation time τ .…”
Section: Working Principlementioning
confidence: 99%
“…After euthanizing the animals, laser speckle images were collected for 5 minutes to obtain a biological zero correction to the CBF measurements. 14 The forepaw stimulation paradigm, which was executed during the time windows marked DA (i.e., data acquisition) in Figure 2, consisted of a train of constant current rectangular pulses (amplitude 1.5 mA, duration 300 ms) delivered to the forepaw at 3 Hz for 4 seconds by a commercial high voltage stimulus isolator (A360; World Precision Instruments). The stimulation train was repeated every 30 seconds for a total time period of 8 minutes.…”
Section: Surgical Preparationmentioning
confidence: 99%